(untitled) (Journal of Oriental Studies, 2017)
It’s very important for each translator to know the role of proverbs and sayings, and collocations in everyday life and in other social spheres of human life, and to determine how often they occur in the practice of translation. Quite often, they are faced with this topic in the translation practice. Awareness about the areas of human activity in which proverbs and sayings, and idioms are particularly frequent, simplifies the work of an interpreter. This article is written based on the research, which was conducted as a survey among translators, and on its results in the form of diagrams.